Features of local immunity in women with endometriosis and genital infection - L. F. Zaynetdinova (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Introduction. External genital endometriosis is an inflammatory estrogen-dependent disease characterized by implantation and proliferation of endometrial tissue outside the uterus, accompanied by increased production of proinflammatory cytokines, prostaglandins, components of the complement, hydrolytic enzymes, increased angiogenesis and anomalies of ectopic endometrium. According to implantation theory, external genital endometriosis develops from viable endometrial cells transferred retrogradely through the fallopian tubes to the abdominal cavity during menstruation, while a disturbed local immunity is an important factor in its pathogenesis. Genital pathogens may be involved in the formation of the immune environment of the peritoneal cavity in women with endometriosis.Purpose. To study the peculiarities of local immunity in women with external genital endometriosis and genital infection pathogens.Materials and methods. 159 women with external genital endometriosis were examined. The total number of leukocytes, the absolute and relative number of viable cells, counts of neutrophils, macrophages and their functional activity, the level of IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IFNα, IFNγ, TNFα in the peritoneal fluid were evaluated. The study of local immunity was performed in women with endometriosis, stage 1—2 and 3—4, depending on detected genital pathogens. Chlamydia trachomatis, Ureaplasma spp., Mycoplasma genitalium, HSV1,2/CMV, high carcinogenic risk HPV were analyzed by using PCR in samples collected from the endometrium, peritoneal fluid, and endometrioid heterotopies. Statistical processing was performed by using the IBM SPSS Statistics Version 22.2 statistical analysis software package.Results. In the presence of HPV and Ureaplasma spp. in women with endometriosis, stage 1—2, the decreased functional activity of peritoneal neutrophils and macrophages was found. At 3—4 stage, a correlation analysis revealed that detected HPV and Ureaplasma spp. obtained increased both pro-inflammatory and anti-inflammatory cytokines in the peritoneum. However, the higher activity of Th-2 cells in the peritoneal fluid secreting IL-4 and IL-10 and suppressing cellular immunity, was observed in HPV-positive samples. In addition, HPV also correlated with a decreased IL-2 and IL-4 levels.Conclusions. The most prominent changes in the immunological parameters from peritoneal fluid samples were observed in case of detected genital infection pathogens, particularly HPV. Thus, immune disturbances emerged upon bacterial and viral pathogen detection may contribute to the implantation of endometrial cells in the pelvic organs and disease progression.